Studies On Malaysian Isolates Of Orf Virus - Al-Ajeeli, Karim Sadun Ali (1995)
This study was conducted to isolate and characterize several orf viruses infecting sheep and goats in Malaysia. The isolates and two reference strains of orf virus were then compared with respect to biological properties, serological properties, protein profile and also DNA profile. Three orf viruses were isolated from infected goats and one from infected sheep. They were identified as orf viruses by means of electron microscope and three serologic tests namely, serum neutralization, immunoperoxidase and immunofluorescent tests. The isolates grew well in cell cultures prepared from goat and sheep, and on chorioallantoic membrane of hen eggs but not in several tested continuous cell lines. Compared to the other two established orf virus strains, cytopathic effect induced by these isolates in kid testis cell culture differed with respect to the time